Knowledge versus content in e-learning: a philosophical discussion - Costa, Gonçalo Jorge Morais da (2014)
Historically education has been supported by technology; however, during the past three decades electronic technologies for educational purposes have been used to achieve better learning outcomes. There are two propositions regarding the use of computers for educational purposes; that is, people can learn“from”technologies or people can learn “with” technologies. The, e-learning literature reveals that technological and instructional perceptions are diffuse. Furthermore, only recently have the ethical and cultural issues been considered. The philosophical discussion within this paper considers these issues and explores the idea of knowledge or content in e-learning, teasing out the differences between these two concepts. In order to contextualize the debate, the literature is reviewed, and a philosophical debate using an inquiry example is presented.